ANOMALIES OF HYOID BONE AND THYROID CARTILAGE: A RARE CASE REPORT (Journal of Forensic Medicine & Toxicology, 2015)
Anomalies of hyoid bone and thyroid cartilage are a feature very rarely encountered in the clinical set up. But in cases of death due to compression of neck they become a crucial criteria to exactly decide and opine about the manner of death. Congenital anomalies of hyoid bone and thyroid cartilage though are a rare entity, when present can be a herculean task for the forensic expert to identify and opine, and not be biased with respect to the manner of death. Hereby presenting a rare case of such entity.
Keywords: Anomaly; Hyoid bone; Thyroid Cartilage